User Perceptions of the campaign Facebook Page: A Mixed Methods Study - James Kite; Bronwyn McGill; Becky Freeman; John Vineburg; Vincy Li; Nathan Berton; Anne Grunseit (Social Media + Society, 2018)
Facebook is used as part of public health communication efforts but little evidence is available on why people engage with health-related Facebook pages and what content appeals to them. This study aimed to investigate user perceptions of and experience with the Make Healthy Normal (MHN) Facebook page, part of a government campaign to address overweight and obesity in adults in New South Wales, Australia. This sequential mixed methods study comprised an online survey ( n  = 591) and six focus groups ( n  = 33) of Facebook users, including both fans (i.e., users who have “liked” the MHN page) and non-fans. We analyzed the online survey descriptively and employed inductive thematic analysis for the focus groups, integrating the two data sources at the stage of interpretation. Our results show that MHN and similar health pages are in demand but that there are a number of contextual and content-related factors that are critical in determining user engagement and over which page administrators have varying levels of influence. Contextual factors, including the drivers for user engagement and Facebook user practices, can be leveraged or managed to influence user engagement but they cannot be controlled. On the contrary, content factors, like the nature of posts, post presentation, and post subject, can be directly influenced by page administrators. Policymakers and practitioners can use these findings to inform the design and operation of their own Facebook pages and should look to conduct and disseminate robust evaluation of their pages to improve user satisfaction and engagement.